Cover Image. Issue 4 (12th March 2020) - Carvalho, Laura A.; Whyte, Shona K.; Braden, Laura M.; Purcell, Sara L.; Manning, Anthony J.; Muckle, Anne; Fast, Mark D.
Abstract : The cover image is based on the Original Article Impact of co‐infection with Lepeophtheirus salmonis and Moritella viscosa on inflammatory and immune responses of Atlantic salmon (Salmo salar) by Laura A. Carvalho et al., https://doi.org/10.1111/jfd.13144 .